A successful obstetric outcome in pregnancy complicated with cor pulmonale, pulmonary hypertension secondary to pulmonary tuberculosis: a case report - Venkatachala, Rao Preethi; Sheela, C. N.; G., Shobha; Devaraj, Uma; Kedlaya, Arpana; Varghese, Kiron (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Pregnancy in patients with pulmonary hypertension and cor pulmonale is associated with high morbidity and mortality. The timing of termination of pregnancy, mode of delivery, labour analgesia and anaesthesia and management during puerperium are challenging issues which need to be resolved. Authors report a case of a 30-year-old primigravida with cor pulmonale and severe pulmonary artery hypertension secondary to past pulmonary tuberculosis, who delivered a healthy baby vaginally, due to its rarity and good outcome. Early diagnosis, effective management of aggravating factors like anaemia and hypertension, informed choice by the couple regarding route of delivery and multidisciplinary approach are the keys to successful outcomes in patients with cor pulmonale.